2018
DOI: 10.1371/journal.pone.0201245
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the cost-effectiveness of an infant 13-valent pneumococcal conjugate vaccine national immunization program in China

Abstract: BackgroundThe burden of pneumococcal disease in China is high, and a 13-valent pneumococcal conjugate vaccine (PCV13) recently received regulatory approval and is available to Chinese infants. PCV13 protects against the most prevalent serotypes causing invasive pneumococcal disease (IPD) in China, but will not provide full societal benefits until made broadly available through a national immunization program (NIP).ObjectiveTo estimate clinical and economic benefits of introducing PCV13 into a NIP in China usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…PCV7 was approved by the Chinese Food and Drug Administration in 2008; however, uptake was low and concentrated in cities. 30 , 31 The administration approved PCV13 for use in infants and children in a 3+1 schedule at 2, 4, and 6 months of age, with a fourth (booster) dose administered at approximately 12–15 months of age in 2016. 31 , 32 However, PCV is currently available only for infants whose parents are able to pay for the vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCV7 was approved by the Chinese Food and Drug Administration in 2008; however, uptake was low and concentrated in cities. 30 , 31 The administration approved PCV13 for use in infants and children in a 3+1 schedule at 2, 4, and 6 months of age, with a fourth (booster) dose administered at approximately 12–15 months of age in 2016. 31 , 32 However, PCV is currently available only for infants whose parents are able to pay for the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 The administration approved PCV13 for use in infants and children in a 3+1 schedule at 2, 4, and 6 months of age, with a fourth (booster) dose administered at approximately 12–15 months of age in 2016. 31 , 32 However, PCV is currently available only for infants whose parents are able to pay for the vaccine. Studies have shown that PCV coverage was around 10% for children aged 2–7 years living in Shanghai, and locals had higher coverage than the floating population.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies assessed the cost-effectiveness of PCV-7 [27,29,30,32,33,39,46], of which one study assessed its effectiveness in the context of typical and pandemic influenza seasons [30]. PCV-13 was assessed in six studies [35,38,40,41,43,45] and comparisons of various types of vaccines were performed in two studies [26,48]. The majority of studies used quality-adjusted life years (QALYs) or disability-adjusted life years (DALYs) as the health outcomes measure [20,25,26,32,[35][36][37][38][39][40][41]44,47,48] while the rest combined both the clinical and the utility outcomes or provided only clinical outcomes, e.g., cases of pneumococcal-related diseases and life years.…”
Section: Methodsmentioning
confidence: 99%
“…The included studies were conducted in 11 Asian countries, including China (n = 7) [26,30,32,33,35,41,48] Malaysia (n = 3) [34,42,44], Hong Kong (n = 3) [28,29,42] Korea (n = 2) [25,46], The Philippines (n = 2) [31,36],Taiwan (n = 2) [27,43], Japan (n = 3) [20,38,39], Thailand (n = 1) [47], Mongolia (n = 1) [45], Bhutan (n = 1) [37], and India (n = 1) [40] (Table 1). One study was a multiple country analysis, performed in Malaysia and Hong Kong [42].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Particularly, we found two studies assessing the cost of measles in the Federated States of Micronesia [49] and the cost of measles and rubella in Romania [50] -a first for measles and rubella in LMIC. Other studies examined further the cost of GE [51][52][53][54][55][56][57][58][59], pneumonia [51,52,[59][60][61][62][63], and influenza [64,65]. Some of them generated COI estimates from a programmatic approach, evaluating the cost of treating diarrhea and pneumonia through an integrated community case management [51,52,59].…”
Section: Limitations Of This Systematic Reviewmentioning
confidence: 99%